KARAKTERISASI MASSA BATUAN DAN EVALUASI KESTABILAN LERENG DENGAN METODE NUMERIK PADA RUAS JALAN PLANJAN–BARON–TEPUS - Tri Puji Astuti; I Gde Budi Indrawan; Didit Hadi Barianto (Direktorat Bina Teknik Jalan dan Jembatan, 2022)
This research aims to evaluate the stability of the slope by considering the rock mass characterization. The research location was conducted on the Planjan–Baron–Tepus section at STA 7+000 to STA 9+725, with limestones dominating the lithology. The data collection method begins with determining rock mass quality based on rock mass classification using the Geological Strength Index (GSI) of limestone introduced by Marinos (2010). The results of testing the physical and mechanical properties of rocks and the quality of rock mass will be used as input parameters in the slope stability analysis. The results showed that the rock mass quality in the research area varied from